2020
DOI: 10.3390/ijms21186736
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antagonistic Effect of Gut Bacteriota Isolated from Indigenous Honey Bees and Essential Oils against Paenibacillus Larvae

Abstract: The aim of study was to isolate and identify the gut bacteria of Apis mellifera and to evaluate antagonistic effect of the bacteriota against Paenibacillus larvae, which causes American foulbrood (AFB) in honeybees. The dilution plating method was used for the quantification of selected microbial groups from digestive tract of bees, with an emphasis on the bacteriota of the bees’ intestines. Bacteria were identified using mass spectrometry (MALDI-TOF-MS Biotyper). Overall, five classes, 27 genera and 66 specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Even insects that inhabit unpolluted environments (e.g., bees and wasps) have a gut microflora that has antagonistic effects against pathogens [ 47 ]. Miroslava et al 2020 isolated and identified the gut bacteria of Apis mellifera and evaluated its antagonistic effect against Paenibacillus larvae, which causes American foulbrood (AFB) in honeybees [ 48 ]. The results of Guzman and Vilcinskas [ 15 ] revealed that the gut bacteria of cockroaches produce active molecule(s) with potent antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Even insects that inhabit unpolluted environments (e.g., bees and wasps) have a gut microflora that has antagonistic effects against pathogens [ 47 ]. Miroslava et al 2020 isolated and identified the gut bacteria of Apis mellifera and evaluated its antagonistic effect against Paenibacillus larvae, which causes American foulbrood (AFB) in honeybees [ 48 ]. The results of Guzman and Vilcinskas [ 15 ] revealed that the gut bacteria of cockroaches produce active molecule(s) with potent antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…bacteria added to sugar syrup at 10 5 CFU/mL concentration. L. kunkeei , Lactobacillus crispatus, and L. acidophilus showed the strongest antagonistic activity against a highly virulent bacterium, P. larvae [ 195 ]. In one study, honeybee larvae and adult bees were administered a mixture of four different strains of L. kunkeei.…”
Section: Lab As a Significant Component Of The Honeybee Microbiotamentioning
confidence: 99%
“…In several studies, essential oils of mint, melissa, coriander and thyme [ 38 ]; other phytochemicals, including caffeine, clove oil, gallic acid, kaempferol and p -coumaric acid; and even propolis showed effective antimicrobial activity, expanded honey bee longevity and, to some extent, reduced nosemosis levels [ 37 , 39 , 40 , 41 , 42 ]. Other natural products tested as additives in honey bee feeding, such as BioPatty, which contains a mixture of Lactobacillus plantarum Lp39, Lactobacillus rhamnosus GR-1 and Lactobacillus kunkeei BR-1, could reduce pathogen loads, up-regulate the expression of key immune genes and improve survival during P. larvae infection [ 43 , 44 , 45 ]. Hydroalcoholic laurel extract [ 12 ], Cinnamomum zeylanicum, Syzygium aromaticum , propolis and Thymus vulgaris are active against M. plutonius [ 46 ].…”
Section: Introductionmentioning
confidence: 99%